Avaliação da integridade do tratamento de um protocolo para redução de estresse em universitários baseado na Terapia de Aceitação e Compromisso (ACT) - Dillenburg, Mariana Sanseverino (2021)
Acceptance and Commitment Therapy (ACT) is a therapeutic approach that aims to develop psychological flexibility through six processes: acceptance, defusion, present moment, SELF as context, values and committed action. ACT already has several randomized clinical trials proving its effectiveness for different mental health issues, including studies with stress in the university population. Therefore, developing interventions that seek to treat stress using an ACT becomes a specific treatment possibility. Treatment Integrity (TI) is a concept that refers to the assessment of competence and adherence to a treatment or intervention. Adherence and competence can be defined as respectively: how much the therapist followed the proposed protocol or theoretical approach and how much he was qualified in his performance. Despite the importance given, the assessment of TI is still often omitted in scientific publications. This dissertation is part of a larger study and aimed to present a program for stress reduction in university students based on ACT. For this, two stuies were carried out, the first was the adaptation of a program and the second was the assessment of the therapists' TI. For the first part, an adaptation of an ACT-based stress reduction program developed at the University of Nevada by Pistorello and colleagues was made with the purpose of becoming a college elective. The evaluation of the viability of this program was part of the larger study. The classes that made up this intervention were recorded for later analysis. For the second part, the TI assessment instrument used was adapted and specialist ACT judges were recruited to assess TI classes. Three classes were selected from the beginning, middle and end of the intervention and each class was analyzed by 3 independent judges. For data analysis, the Fleiss kappa coefficient and the Friedman test were used. The results hindered that the therapists who participated in the program had an excellent adherence to the protocol and a good adherence to ACT. Therapists had more adherence to the psychological flexibility processes more focused in each class. Therapists also scored well on the competency factor in each class. This study sought to bring ways of working with prevention in universities and to provide the therapy community with tools to put the intervention into practice. Because it was a small sample, future studies are needed with those that improve the TI assessment instrument.